Mind–body therapy for cardiometabolic risk in U.S. middle-aged Black adults: a scoping review - Martin, Danielle A.; Hook, Jane; Kim, Sunny Wonsun; Larkey, Linda; Lee, Rebecca E. (Frontiers in Public Health, 2025)
BackgroundIn the U.S., Black adults do not achieve the same life expectancy as their White counterparts, and this is attributable in large part to the development of cardiovascular disease (CVD). Mind–body therapy (MBT) interventions demonstrate improvements in cardiometabolic risk (CMR) factors that promote CVD, with increased feasibility and acceptability in the general population. Less known is the feasibility, acceptability, and evidence of reduction in CMR factors in the U.S. Black population with MBT.PurposeThis study aimed to synthesize the current state of research regarding MBT on CMR factors in middle-aged U.S. Black adults and identify gaps in the literature. Research Question 1: What types of studies have been conducted (study design, theoretical framework, and cultural relevance)? and Research Question 2: What is the feasibility and acceptability and effectiveness of MBT in Black adults for CMR reduction?MethodsFollowing PRISMA-ScR guidelines, a review of three databases was conducted. Our inclusion criteria were articles that (1) describe empirical research; (2) assessed a MBT intervention in middle-aged (35–64) adults with a minimum of 60% Black adult participants for CMR reduction; and (3) written in English. Independent reviewers selected articles for inclusion and data extraction, with a third reviewer providing consensus.ResultsFourteen articles met the eligibility criteria (n = 14). Characteristics included randomized controlled trials (8, 57.1%); single-arm (3, 21.0%); mixed methods (3, 21.0%); sample size (17–375); mean age range 43–64; female (6, 42.8%); theoretical framework (4, 28.6%); culturally adapted (7, 50.0%); and studies demonstrating feasibility and/or acceptability (7, 50.0%). Of the seven articles assessing CMR physiologic factors, five studies observed significant improvement. For the 11 studies assessing CMR psychological factors, 6 studies had statistically significant results and 3 studies identified trends toward positive statistical outcomes.ImplicationA growing body of literature across research stages demonstrating acceptability, and feasibility, and evidence of effectiveness for selected outcomes of MBT in middle-aged Black adults with CMR factors shows promise. Future research recommendations include greater recruitment of Black men for MBT studies, larger sample sizes, and utilizing culturally adapted interventions for engaging Black adults in MBT for reduced CMR factors.